Survival following screening and preemptive antifungal therapy for subclinical cryptococcal disease in advanced HIV infection. (1st October 2021) - Makadzange, Tariro Azure; Hlupeni, Admire; Machekano, Rhoderick; Boyd, Kathryn; Mtisi, Takudzwa; Nyamayaro, Primrose; Ross, Christine; Vallabhaneni, Snighdha; Balachandra, Shirish; Chonzi, Prosper; Ndhlovu, Chiratidzo Ellen
Abstract : Objectives: Our study's primary objective was to compare 1-year survival rates between serum cryptococcal antigen (sCrAg)-positive and sCrAg-negative HIV-positive individuals with CD4 + cell counts less than 100 cells/μl without symptoms of meningitis in Zimbabwe. Design: This was a prospective cohort study. Methods: Participants were enrolled as either sCrAg-positive or sCrAg-negative and followed up for 52 weeks or less, with death as the outcome. Lumbar punctures were recommended to all sCrAg-positives and inpatient management with intravenous amphotericin B and high-dose fluconazole was recommended to those with disseminated Cryptococcus. Antiretroviral therapy was initiated immediately in sCrAg-negatives and after at least 4 weeks following initiation of antifungals in sCrAg-positives. Multivariable logistic regression models were used to determine risk factors for mortality. Results: We enrolled 1320 participants and 130 (9.8%) were sCrAg positive, with a median sCrAg titre of 1 : 20. Sixty-six (50.8%) sCrAg-positives had lumbar punctures and 16.7% (11/66) had central nervous system (CNS) dissemination. Cryptococcal blood cultures were performed in 129 sCrAg-positives, with 10 (7.8%) being positive. One-year (48–52 weeks) survival rates were 83.9 and 76.1% in sCrAg-negatives and sCrAg-positives, respectively, P  = 0.011. Factors associated with increased mortality were a positive sCrAg, CD4 + cell count less than 50 cells/μl and having presumptive tuberculosis (TB) symptoms. Conclusion: Our study reports a high prevalence of subclinical cryptococcal antigenemia and reiterates the importance of TB and a positive sCrAg as risk factors for mortality in advanced HIV disease (AHD). Therefore, TB and sCrAg screening remains a crucial component of AHD package, hence it should always be part of the comprehensive clinical evaluation in AHD patients. Abstract : Supplemental Digital Content is available in the text